Investigation on the Effect of Lime and Fly Ash on Hydraulic Conductivity of Soil - Amiralian, Saeid; Chegenizadeh, Amin; Nikraz, Hamid (Planetary Scientific Research Centre, 2012)
This paper presents a series of laboratory experiments in order to investigate on the effect of lime and fly ash on hydraulic conductivity of sand. The study were conducted on Baldivis Yellow Concrete Sand (The Western Australian sand) with different percentage of lime (%1, 2%, 3%), fly ash (%5, %10, %15) and composition of lime and fly ash. A few researches carried out in this field however, the result of current study revealed an effective role of lime and fly ash in the reduction of hydraulic conductivity of sand. The obtained results illustrated that, in compared with the other results of lime and fly ash specimens the combination of lime and fly ash had a significant reduction in hydraulic conductivity of sand. Hence, it seems that utilization of the combination of lime and fly ash was more effective than use additives alone (i.e., lime and fly ash).